Releasing CSS - Schmitt, Christopher (O'Reilly short cuts., 2006)
In an industry that communicates with terms such as "Browser Hell" and "browser wars," a web designer can be excused for having some anxiety over Microsoft's recent upgrade of Internet Explorer 6 (IE6) to Internet Explorer 7 (IE7). Web designers should ask the following questions: What problems does IE6 possess and what fixes does IE7 provide? What part of the Cascading Style Sheets (CSS) specification does IE7 for Windows support? How can web designers work around any problems that exist within IE7's support for CSS? While web designers are testing their designs on the latest browser, how fast will IE7 be adopted by their client's audience? This Short Cut attempts to answer these questions to allow web designers a smoother transition to IE7 and, hopefully, an escape from Browser Hell. Visit the catalog page for Releasing CSSVisit the errata page for Releasing CSS.